Social Safety and Security - Chliaoutakis, Joannes (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Social safety in social environments entails the sense of feeling safe with other people. Thus, social safety and security are very important to our life. Although research in this area has made significant progress in the past few years, there are still many social problems that require attention and further development in order to secure peace of mind. There is a very clear and accurate understanding and judgment of the overall situation of social security in the current and future period. This Special Issue focuses on a number of contemporary issues in social safety and security. The objective of this book is to rapidly disseminate the latest research and knowledge in this important area.